HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG KONSUMSI TABLET FE DENGAN KEJADIAN ANEMIA - Erlina Esther siringo ringo (Universitas Prima Indonesia, 2022)
Iron in pregnant women is a health problem experienced by women around the world. WHO also reports that the prevalence of pregnant women who experience iron deficiency is around 35-75% and increases with increasing gestational age 2021. The aims of the study is to know the relationship of knowledge level of pregnant women about fe tablet consumption with anemia events. This type of researchis quantitative with a descriptive correlation design, which uses a cross sectional study approach. The place of this research was carried out in Pulau Simardan Village, Tanjungbalai City in 2021, the data collection tool used was a questionnaire. The population in this study amounted to 40 people so that the entire population was used as a sample. The results of this study indicate that the majority of pregnant women's level of knowledge about the consumption of Fe tablets is in the sufficient category, as many as 22 people (55%). The majority of pregnant women did not experience anemia, as many as 22 people (55%). There is a significant relationship between the level of knowledge about the consumption of Fe tablets with the incidence of anemia in Pulau Simardan Village, Tanjungbalai City in 2021, the results of the Chi-Square test obtained p value = 0.000 (p <0.05). It is hoped that the puskesmas will naturally increase the outreach activities about the benefits of Fe tablets and the dangers of anemia in pregnancy so as to increase the knowledge of pregnant women. Pregnant women in Pulau Simardan Village are expected to maintain food intake and consumption of Fe tablets during pregnancy so as to reduce the risk of anemia during pregnancy